Assessment of acoustic and mechanical properties in modified rubberized concrete - Algaifi H.A.; Syamsir A.; Baharom S.; Alrshoudi F.; Qaid A.; Al-Fakih A.M.; Mhaya A.M.; Salah H.A. (Elsevier Ltd, 2025)
Utilizing waste crumb rubber and substituting cement in concrete with industrial waste materials, such as ground granulated blast furnace slag (GBFS), represents a promising pathway towards achieving sustainable development. This study assesses the inclusion of waste rubber powder (RP) alongside graphene nanoplatelets (GnPs) and an efficient surfactant (Tween 80), in conjunction with GBFS in concrete, in terms of acoustical and mechanical properties. The RP content varied from 4 % to 18 % as a replacement for sand, while GnPs (0.1 % to 0.7 %) and GBFS (30 %) were utilized as substitutes for cement. The compressive (CS), flexural (FS), tensile strength (TS), sound absorption (), and noise reduction coefficient (NRC) of the modified rubberized concrete were experimentally and theoretically evaluated. The outcomes revealed that the optimum content of RP and GnPs was 11 % and 0.4 %, respectively, in which the CS, FS, and TS were 49.5 MPa, 6.3 MPa, and 2.7 MPa, respectively, compared to the control mix (45.5 MPa, 5.2 MPa, and 2.5 MPa). In addition, the sound absorption and noise reduction coefficient of the modified rubberized concrete were 0.556 at a frequency of 1760 Hz and 0.16, respectively, compared to the control mix (0.53, 0.109), while the highest value of (0.603) was achieved when the rubber content was 18 %. It can be concluded that the proposed concrete mixture fulfilled the requirements of both mechanical and acoustical properties as well as enhanced sustainability by addressing waste disposal and minimizing CO2 emissions. It also suggests a feasible direction for further exploration into its performance under elevated temperatures and aggressive environmental conditions. ? 2024 The Authors